Elementi di scatologia pasoliniana in Petrolio/Vas - Gallina, Francesco (L'ospite ingrato, 2024)
In Pier Paolo Pasolini’s Petrolio/Vas, Urine and Feces are the two “powers” represented by the two astronauts protagonists of the Storia di un volo cosmico in Note 102a, which stages the close interdependence between urethral and anal eroticisms on which Note 102 (Storia di due padri e di due figli) is more explicitly based. In a view of cosmic sexualization, Pasolini’s “world work” endows itself with genital properties, ascribing psychoanalytic and political values to urine and feces which this essay sets out to examine starting from the motifs of puer mingens and homo cacans, analyzing in particular the influences exerted on Pasolini by the Freudian theories, the Sándor Ferenczi’s bioanalytic researches and the Studies in Anality in Norman O. Brown’s Life Against Death.